Analisis Pengaruh Kualitas Pelayanan dan Inovasi Produk Endoskopi di bagian Penyakit dalam terhadap image rumah sakit pada rumah sakit umum daerah (RSUD) Tugurejo Semarang - Hernawati Indah Retno; Ekowanti Ekowanti Ekowanti (Semantik, 2011)
ABSTRACT: the improvement of public knowledge on health services increases their attentions toward the industry of health care service. Besides giving maximum health care service, a health care institution should be able to apply the most advanced technology in order to fulfill the major requirement in a competition to serve a much better health care service in the community. This research tends to acquire empirical evidences of the effects of service quality and product innovation on The District General Hospital Tugurejo Semarang.Keyword: satisfaction, customer, health care service, hospital